Caracterización de la calidad, capacidad y precio como factores determinantes de la competitividad del aguacate Hass en los municipios Filandia, Salento y Pijao del departamento del Quindío con destino a mercados internacionales (2016)
The next research titled “Characterization of the quality, capacity and price as determinant factors of the competitiveness of Hass avocado in the department of Quindío principally destined to international markets” has as intention to describe the three factors that influence in the region’s competitiveness doing an analysis of the correlation between the factors quality, capacity, price and the legal requirements of the international markets, taking into account that currently there are an unsatisfied demand of Hass avocado on the foreign market and it represents an opportunity for the department according to the comparative and competitive advantages that it has. The methodology used it for this research will be descriptive with a mixed method to ensure the description of the factors according to the data collected by the producers and exporters of the department.